Single-cell and spatial transcriptome profiling reveal CTHRC1+ fibroblasts promote EMT through WNT5A signaling in colorectal cancer - Yunfei Lu; Yang Chen; Zhenling Wang; Hengyang Shen; Lei Xu; Changzhi Huang; Ying Tong; Yu Shao; Hongqiang Zhang; Zan Fu (Journal of Translational Medicine)
Abstract Background Cancer-associated fibroblasts (CAFs), known for facilitating the progression and metastasis of colorectal cancer (CRC), have become a promising therapeutic target. However, the significant heterogeneity of CAFs and their intricate crosstalk with tumor cells present substantial challenges in the development of precise and effective therapeutic strategies. Methods Single-cell RNA sequencing (scRNA-seq) technology was used to identify various cell subtypes. Spatial transcriptomics (ST) was employed to map the spatial niches and colocalization patterns of these cell subtypes. Cell-cell interactions among these subtypes were analysed via CellChat and NicheNet software. Tumor cell invasion, migration, and proliferation were assessed through wound healing assays, transwell assays, colony formation assays, and xenograft mouse models. Results We identified a significant spatial colocalization between CTHRC1+ CAFs and a distinct subtype of malignant epithelial cells, both residing within the EMT-active spatial niche. Our results demonstrate that CTHRC1+ CAFs, as a major source of WNT5A, promote epithelial-mesenchymal transition (EMT) and enhance tumor cell invasiveness by upregulating MSLN expression in adjacent malignant epithelial cells. This signaling axis contributes significantly to CRC progression and metastasis. Conclusions Targeting the CTHRC1+ CAF-WNT5A-MSLN signaling axis presents a promising therapeutic strategy for advanced CRC patients. Our study provides new insights into the role of CAFs in CRC progression and offers potential avenues for developing targeted therapies to disrupt this pathway.